Rasch Model Analysis to Identify Students’ Self-Efficacy and Learning Interest and Uncover Their Influence on Student Learning Outcomes in Static Fluids - Uci Fatonah; Maison Maison; Ervan Johan Wicaksana; Ilham Falani (Universitas Lambung Mangkurat, 2023)
This study explores the relationship between self-efficacy, students' interest, and physics learning outcomes for students in classes XI IPA 1 and XI IPA 2 at SMA Negeri 16 Bungo. The learning outcomes are focused on the dimensions of conceptual and factual knowledge. Data on students' self-efficacy and interest were collected through a structured scale questionnaire, while data on students' learning outcomes in conceptual and factual knowledge were obtained through test instruments. The results indicate a positive correlation between students' self-efficacy, interest in learning, and physics learning outcomes. The correlation coefficient (r value) obtained is greater than the critical r value, with significance less than 0.05. Regression analysis reveals that the calculated F value is greater than the critical F value, and the calculated t value is greater than the critical t value, both with significance less than 0.05. Regression analysis also shows that self-efficacy and students' interest in learning affect physics learning outcomes by 68%, leaving 32% influenced by other factors not investigated in this study. For teachers, this research provides practical insights into the importance of developing students' self-efficacy and interest in the context of physics learning. By considering these aspects, teachers can design more effective teaching strategies to support students' optimal development in physics learning. In the theoretical framework, these findings support the concept that internal factors such as self-efficacy and interest play a crucial role in achieving good learning outcomes.